2010
DOI: 10.1371/journal.pone.0013858
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hepatic Gene Expression upon Oral Administration of Taurine-Conjugated Ursodeoxycholic Acid in ob/ob Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is highly prevalent and associated with considerable morbidities. Unfortunately, there is no currently available drug established to treat NAFLD. It was recently reported that intraperitoneal administration of taurine-conjugated ursodeoxycholic acid (TUDCA) improved hepatic steatosis in ob/ob mice. We hereby examined the effect of oral TUDCA treatment on hepatic steatosis and associated changes in hepatic gene expression in ob/ob mice. We administered TUDCA to ob/ob mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 49 publications
2
38
1
4
Order By: Relevance
“…In contrast, activation levels of JNK in liver of Pkr −/− ob/ob mice were significantly lower than those detected in Pkr +/+ ob/ob controls. Similarly, the increased eIF2α phosphorylation seen in the liver of ob/ob mice in numerous independent studies (Ozcan et al, 2004; Sreejayan et al, 2008; Tsutsumi et al, 2011; Yang et al, 2010) was significantly reduced to levels close to lean controls upon loss of PKR (Figure 5G). Of note, activation of PERK, the ER resident eIF2α kinase, remained elevated in liver of Pkr −/− ob/ob mice (Figure S4D).…”
Section: Resultsmentioning
confidence: 60%
“…In contrast, activation levels of JNK in liver of Pkr −/− ob/ob mice were significantly lower than those detected in Pkr +/+ ob/ob controls. Similarly, the increased eIF2α phosphorylation seen in the liver of ob/ob mice in numerous independent studies (Ozcan et al, 2004; Sreejayan et al, 2008; Tsutsumi et al, 2011; Yang et al, 2010) was significantly reduced to levels close to lean controls upon loss of PKR (Figure 5G). Of note, activation of PERK, the ER resident eIF2α kinase, remained elevated in liver of Pkr −/− ob/ob mice (Figure S4D).…”
Section: Resultsmentioning
confidence: 60%
“…Because lipotoxicity impairs ER function and leads to a prolonged unfolded protein response, which can engage stress and inflammatory pathways, it may also be considered for potential intervention strategies. The use of agents that alleviate ER stress, such as tauroursodeoxycholic acid (TUDCA) and 4-phenylbutyric acid, has been tested in metabolic contexts with beneficial results on liver and CNS function (153,(233)(234)(235). TUDCA treatment in experimental models of acute pancreatitis and ischemia reperfusion in liver also demonstrated decreased JNK activity along with attenuated inflammatory responses (236,237).…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, modulation of ER stress improved hepatic steatosis with a restoration of glucose homeostasis and insulin sensitivity in the diabetic mouse. 9,10 A recent epidemiological study using data from the National Health and Nutrition Examination Survey revealed that uric acid was associated with NAFLD independently of metabolic syndrome. 11 Additional studies have shown that elevated serum uric acid is an independent predictor of NAFLD.…”
mentioning
confidence: 99%